Joystick controlled autonomous robotic arm using inverse kinematics with object detection - Aldea, Edmark Jayson Q. (Animo Repository, 2022)
In 2019, the Novel Coronavirus Disease (COVID-19) has been categorized as a pandemic. This disease can be transmitted via droplets that stay on items or surfaces within a specific number of hours. Which is why the researchers aimed to develop a wirelessly controlled robot arm and platform capable of picking up objects detected via object detection. Robot arm movements are done via the use of inverse kinematics. Meanwhile, a custom object detection model that can detect objects of interest will be trained and implemented in this project. To achieve this, the researchers utilize various open-source libraries, microcontrollers, and readily available materials to construct and program the entire system. At the end of this research, the prototype was capable of reliably detecting objects of interest along with a grab and dispose success rate of 88%. Instruction data can be properly sent and received, and dual webcam image transfer reaches up to 1.72 frames per second.